Agile Scrum course : Scrum fundamentals : Scrum certification - Rubio, Mauricio (Packt Publishing, 2019)
"Scrum is the most popular agile methodology for delivering projects. It's an iterative, time-boxed approach or framework to solve problems & deliver value. Scrum focuses on speed, simplicity and continuous improvement whilst remaining completely customer-centric. This course covers: The Difference between Agile Scrum Project Management and Traditional Project Management; Why Scrum is so powerful; Scrum Concepts; Scrum Fundamentals; Scrum Tools and Artifacts; Scrum Pillars; Scrum Values; Scrum Rituals; The Meaning of User Stories; The Origins of Scrum; How to Work with Scrum; How to Succeed in your Scrum Projects."--Resource description page